Cognitive and affective daily life predictors for the course of recurrent depression and the impact of mindfulness-based attention training: an ambulatory assessment study - Timm, Christina (2019)
Daily life microlevel processes, assessed with Ambulatory Assessment (AA) have recently shown to contribute to a better understanding of macrolevel syndromes and constitute potential AA-phenotypes influencing onset and course of recurrent depression. Further, cognitive risk factors, such as rumination, have been shown to be linked to impaired attentional processes in remitted depressed (rMDD) individuals, presumably resulting in an increased risk of relapse. Mindfulness-Based Interventions aim to improve attentional processes in rMDD individuals and effectively reduce relapse risk in recurrent depression. Based on a longitudinal investigation (Study 1) and a Randomized Control Trail (RCT, Study 2) the present thesis investigated cognitive and affective AA-phenotypes as predictors for the long-term course of recurrent depression and examined effects of a Mindfulness-Based Attention Training (MBAT) on respective daily life processes. Study 1 aimed to investigate the impact of cognitive and affective AA-phenotypes on the long-term symptom course in 57 recurrently depressed individuals during a three-year follow-up interval. Level and instability of baseline AA variables were aggregated and used as predictors for time to relapse, chronicity, and maintenance of depressive symptoms thereby combing AA data with longitudinal macrolevel outcomes. Results of Study 1 indicate that daily life affective instability predicts time to relapse, while instability of daily life rumination appears to influence persistence of depressive symptoms over a three-year interval in recurrently depressed individuals. These findings support the assumption that cognitive and affective daily life processes may represent important AA-phenotypes that are prospectively linked to clinical outcomes in depression. Study 2 investigated short-term effects of a four-week Mindfulness-Based Attention Training (MBAT) compared to an active control training (Progressive Muscle Relaxation – PMR) on cognitive and affective AA-phenotypes in a new sample of 78 remitted depressed (rMDD) individuals. Both trainings were highly standardized and AA-outcomes (positive and negative affect, rumination and self-acceptance) were assessed three days before and after trainings each with 10 assessments per day. The RCT study identified significant intervention effects demonstrating a beneficial influence of MBAT compared to PMR on all AA-outcomes with reduced negative affect and rumination and increased positive affect and self-acceptance. The beneficial effects of MBAT were particularly evident in those individuals with more previous episodes and therewith those at highest vulnerability for relapse. Thus, respective changes in cognitive and affective states may reflect potential mechanisms of action in mindfulness-based intervention research. Both studies offer new insights into the understanding of daily life cognitive and affective AA-phenotypes as potential vulnerability factors of recurrent depression and their changeability through appropriate interventions.
Keywords: Hochschulschrift